O estágio e a formação dos futuros docentes de Biologia: a participação dos professores da escola básica - Magalhães, Caroline Arantes (2018)
Grounded on the mapping of research production on supervised internship in teacher education, especially for the formation of Biology teachers, and on the reality of recent political actions regarding internship for which the legislation points to the increased value of practice in professional formation, actions of basic school teachers have been noticed to be an object of study which enables researchers to learn the characteristics of these basic education professionals and should help Biological Sciences teachers-to-be to get into the school reality. Thus, the present research aims to discuss the actions of these co-teacher educators and investigate how they perceive their role as educators and in which conditions their practice is developed. This study is grounded on Pierre Bourdieu’s concept of habitus and on the sociological concepts of experience and logic of actions proposed by François Dubet to understand different dispositions acquired by the teachers. The central hypothesis of this work focuses on understanding the possibility teachers have to report and analyze their experiences in the profession involving life at school and, by doing so, identify the characteristics of their relationship with internees as well as the real contribution of supervised internship to prepare new Biology teachers to start the career. Four major axes of analysis were used to examine the information gathered in the field (choice and entry into the profession, education and action contexts, and self-perception). Patterns were found in the statements, in the expressed forms of thought and in the behaviors of the participants, teachers who acted as supervisors. Many influential factors and a great complexity in their articulation were found in their actions. Relationships among the choice to take up an undergraduate course in Teaching of Biological Sciences, the beginning of experiencing supervised internship, learning the profession, professional trajectories, current positions in the labor market, pedagogical actions and their personal and professional experiences are connected and configure the way each one perceives his work and how they perceive themselves in relation to their internees’ education. It was found that the participants of this research could not recognize themselves as teacher educators, nor did they develop autonomy of thought in relation to the possibility they have, and the condition that the supervisory role gives them to report and analyze their professional experiences in order to contribute socially to the formation of less unprepared Biology teachers